From Intense to Leisurely Study Days: A Diary Study of Daily Wellbeing among Students in Higher Education - Moilanen Sanna; Autio Laura; Tolvanen Asko; Sevón Eija; Rönkä Anna (De Gruyter, 2020)
This mobile diary study examined day-today variability during one study week among university students and study-related associated factors promoting and impairing their well-being. Specifically, we explored (1) what factors university students consider as promoting and as impairing their daily wellbeing, (2) what types of daily study profiles for students can be identified based on study hours, study motivation, and academic stress, and (3) how the factors promoting and impairing students' daily wellbeing are related to these daily study profiles. The study utilized one-week mobile diary data collected from 86 university students studying in a Finnish university (a total of 602 measurements). Seven factors promoting and eight factors impairing the wellbeing of students were identified. These included leisure time and domestic duties, social relations, sleep, rest, nutrition, and time management. Using multilevel latent profile analysis, we further identified four distinct daily study profiles: intense, productive, inefficient, and leisurely study days. The results also showed that the various factors promoting and impairing daily wellbeing were differently associated with the four study profiles.